A Novel ATP-Binding Cassette Transporter Involved in Multidrug Resistance in the Phytopathogenic Fungus Penicillium digitatum - Nakaune, Ryoji (American Society for Microbiology, 1998)
Demethylation inhibitor (DMI)-resistant strains of the plant pathogenic fungus Penicillium digitatum were shown to be simultaneously resistant to cycloheximide, 4-nitroquinoline-N-oxide (4NQO), and acriflavine. A PMR1 (Penicillium multidrug resistance) gene encoding an ATP-binding cassette (ABC) transporter (P-glycoprotein) was cloned from a genomic DNA library of a DMI-resistant strain (LC2) of Penicillium digitatum by heterologous hybridization with a DNA fragment containing an ABC-encoding region from Botrytis cinerea. Sequence analysis revealed significant amino acid homology to the primary structures of PMR1 (protein encoded by the PMR1 gene) and ABC transporters of Saccharomyces cerevisiae (PDR5 and SNQ2), Schizosaccharomyces pombe (HBA2), Candida albicans (CDR1), and Aspergillus nidulans (AtrA and AtrB). Disruption of the PMR1 gene of P. digitatum DMI-resistant strain LC2 demonstrated that PMR1 was an important determinant of resistance to DMIs. The effective concentrations inhibiting radial growth by 50% (EC(50)s) and the MICs of fenarimol and bitertanol for the PMR1 disruptants (Δpmr1 mutants) were equivalent to those for DMI-sensitive strains. Northern blot analysis indicated that severalfold more PMR1 transcript accumulated in the DMI-resistant strains compared with those in DMI-sensitive strains in the absence of fungicide. In both DMI-resistant and -sensitive strains, transcription of PMR1 was strongly enhanced within 10 min after treatment with the DMI fungicide triflumizole. These results suggested that the toxicant efflux system comprised of PMR1 participates directly in the DMI resistance of the fungus.